Analysis of Differences in Well Water Quality Tests in the Highlands and Lowlands of Rantauprapat City - Harahap, Arman (Publisher Cv. Inara, 2023)
The existence of clean water is very important considering the very dynamic activities of people's lives. Therefore, the quality and quantity must be considered. Clean water that meets health requirements must be free from pollution and must meet quality standards: one of them is physical requirements because drinking water that does not meet quality standards can cause health problems. The topography of an area can affect groundwater in that area. This study aims to analyze differences in the quality of well water in the highlands of Rantauprapat City and the lowlands of Rantauprapat City based on physical parameters. The research was conducted at the BTKL Physics Laboratory in Medan in October 2022. The method in this research was observational analytic with a cross-sectional approach. The sample was determined by purposive sampling which amounted to 50 samples. Data were analyzed using SPSS 21 and the Mann Whitney-U Test. The results showed that there was no significant difference in water quality in the parameters of taste, temperature, odor and turbidity with a p value > 0.05, while there were significant differences in the parameters TDS and DHL with a p value <0.05. Conclusion: There are no significant differences in water quality in the parameters of taste, temperature, odor and turbidity, while in the TDS and DHL parameters there are significant differences in water quality with a p value <0.05. 0.05 while the TDS and DHL parameters are significantly different with a p value <0.05. Conclusion: There are no significant differences in water quality in the parameters of taste, temperature, odor and turbidity, while in the TDS and DHL parameters there are significant differences in water quality with a p value <0.05. 0.05 while the TDS and DHL parameters are significantly different with a p value <0.05. Conclusion: There are no significant differences in water quality in the parameters of taste, temperature, odor and turbidity, while in the TDS and DHL parameters there are significant differences in water quality with a p value <0.05.